Sociodemographic factors and living conditions of pediatric burn patients - Ozer Ozlu; Abdulkadir Basaran (Paediatrica Indonesiana, 2022)
Background Children are the age group most vulnerable to burn injuries. Socioeconomic factors and the living environment, including the poor living conditions faced by refugees, may contribute to the occurrence of burns. Objectives To compare living conditions and socioeconomic status potentially contributing to burn injury, characteristics, access to medical treatment, and integrated preventive measures between children of Turkish families and Syrian refugees with burn injuries. Methods In this cross-sectional study, we recorded demographic and epidemiological features, mechanism of burn injury, as well as living- and socioeconomic conditions from interviews with parents of children hospitalized in the Burn Center of the University of Health Sciences Adana City Training and Research Hospital, Adana, Turkey. We classified patients into Turkish (host country) and Syrian (refugee) children. Results We studied 42 Turkish and 31 Syrian children with burn injuries. The most common heat source was a stove (93.2%) and the most common place of the accident was the kitchen (45.2%). Maternal education (P=0.022), house ownership (P<0.001), number of rooms in the house (P=0.001), number of household members (P=0.007), number of persons per room (P<0.001), and place of heat source (P=0.009) differed significantly between Turkish and Syrian patients. Mean number of household members was 5.38 persons (SD 1.0) and 6.81 persons (SD 0.9) in Turkish and Syrian patients, respectively (P=0.007). Conclusion Low socioeconomic status with overcrowded living conditions is prominent in both groups. Burns are likely to occur in the kitchen and incited by a stove. Preventive strategies are needed to educate families on the importance of simple safety measures in the house.